The effect of caring work environment model on nurses’ burnout in general hospitals - Kuswantoro Rusca Putra; Heriandi Sutadi; Setyowati Setyowati; Rr. Tutik Sri Hayati (International Journal of Public Health Science (IJPHS), 2021)
Nurses belong to a profession that carries a high risk of burnout. This condition will have an impact on the performance and quality of nursing services. Efforts should be made to minimize burnout for nurses. Management of the nurses' work environment is one that should be done by the nurse manager. This study aimed to identify the effect of the implementation of a caring work environment by the head of the care unit on nurse burnout. This study used a quasi-experimental design with a pre- and post-test with control group approach. Respondent of this study was 170 nurses who were divided into intervention and control groups. The intervention group consisted of nurses within the Caring Work Environment Model as applied by the head of the units. The control group included nurses working in the environment commonly applied in accordance with hospital policies in the inpatient unit. Burnout measurements on nurses applied preand post- intervention. Data analysis was performed using the Mann Whitneytest. This research showed a decrease in emotional fatigue and depersonalization scores, and an increase in nurse personal accomplishment, (p<0.001) after the implementation of the nurse's caring work environment model by the head of care unit in the intervention group. Within the control group, only personal accomplishment showed increased scores, (p=0.034). Reduction in burnout symptoms in nurses can be facilitated through the implementation of a caring work environment by the head of the care unit.